The Effect of Balanced Scorecard Measurement of Financial Perspective, Customers, Internal Business Processes, Learning and Growth on Company Performance - Suprihati Suprihati (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
The purpose of this study was to determine the effect of partial and simultaneous financial perspectives, customer perspectives, internal business perspectives and growth and learning perspectives on the performance of Parama Indonesia Inc., with a sample of 33 respondents. The data analysis technique uses multiple linear regression analysis. From the partial results, it is known that the financial perspective variable has a tcount of 2.677 greater than t table of 2.048 with a significance value of 0.012 <0.05; this means that the financial perspective has a partial effect on the performance of the Parama Indonesia Inc. The customer perspective variable has a t value of 3.401 greater than t table of 2.048 with a significance value of 0.002 <0.05; this means that the customer's perspective has a partial effect on the performance of the Parama Inc Indonesia Inc. The internal business process perspective variable has a calculated value of 2.461 greater than t table of 2.048 with a significance value of 0.020 <0.05; this means that the perspective of internal business processes has a partial effect on the performance of Parama's Indonesia Inc. The variable perspective of growth and learning has a t value of 2.362 greater than t table of 2.048 with a significance value of 0.025 <0.05; meaning that the growth and learning perspective has a partial effect on the performance of Parama's Indonesia Inc. Simultaneous results obtained Fcount value of 33,957> Ftable (2,71) with a probability of 0,000 (p value <0,05). This means financial perspective, customer perspective, internal business perspective, learning and growth perspective simultaneously affect the performance of Parama's Indonesia Inc.